The Importance of Monitoring Urban Sprawl in Cities, And the Appropriate Ways to Measure It: أهمية مراقبة الزحف العمراني في المدن والطرق المناسبة لقياسه - Hadeel Khanji, Abed Elkader Hariri, Maad El-Madlaji (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2022)
Urban sprawl is a common phenomenon in both developed and developing countries and most city planners agree that urban sprawl threatens the sustainability of urban growth. There is a clear contradiction between the benefits achieved by a small group who benefit from urban sprawl to improve their level of living, and the problems of the majority that are affected by their quality of life due to arrivals to the sprawl areas (environmental, traffic and planning problems and other problems). Therefore, it was necessary to monitor measure and analyze urban sprawl and land-use maps’ change, in order to prioritize planning policies and solutions necessary to be addressed. This situation attracted more attention and modern and advanced studies using geographic information systems and remote sensing techniques, which proved to a large extent to be an effective and valuable tool for monitoring and evaluating urban sprawl over a period of time. There are several measures and methods used to determine the changes of land use and to measure the urban sprawl of cities; However, many of them suffer from many limitations and difficulty in accessing data for its application. In this research, we first provide a definition of urban sprawl, its characteristics, causes, and measurement techniques that have been applied in many countries from decades to the present. The research will discuss its advantages and disadvantages, in addition to explaining the most appropriate way to measure and monitor land use changes in the vicinity of cities, so that planners can implement the appropriate policies to effectively reduce this phenomenon.